Designing compelling accommodationscapes: Testing a framework in a rural context. (July 2021) - Agapito, Dora; Pinto, Patrícia; Ascenção, Mário Passos; Tuominen, Pasi
Well-designed experiencescapes are deemed a key factor in the marketing of tourist experiences aiming at positive tourists' responses. However, this aspect has been underrepresented in empirical research focused on accommodation businesses. This study proposes the construct compelling accommodationscape and empirically tests a theoretical framework in a rural context through the lens of experiential marketing. The proposed construct is presented as the external stimuli that underlie an engaging context of the guest experience in lodging units, based on the idea that a holistic approach to stimuli can evoke interest and attention; and, subsequently, act as a driver to positive action. Apart from physical stimuli and staff performance, which have been the factors more commonly examined in services marketing, the construct compelling accommodationscape extends the servicescape approach by also addressing product-related factors, the existence of a theme and social interactions. Structural equation modelling applied to data from a survey administered in rural lodgings in Southwest Portugal supports that the five external factors underlie the proposed construct. In turn, compelling accommodationscape is positively related to tourists' satisfaction and positive behavioural intentions. Theoretical and practical implications are provided for scholars and rural accommodation managers.